Contesting Big Brother: Legal Mobilization against Workplace Surveillance in the Puretex Knitting Company Strike, 1978–1979 - Godden, Mason (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2020)
In 1978, over 200 textile workers affiliated with Local 560 of the Canadian Textile and Chemical Union went on strike at Puretex Knitting Company, a small garment factory in Toronto, Ontario. Of the strikers, 190 were immigrant women who opposed management’s installation of nine security cameras on the premises, one of which was trained on the entrance to the women’s washroom. To have the cameras removed and win the strike, Local 560 used a combination of traditional strike tactics and legal mobilization. This article makes a case for the significance of the Puretex strike by arguing that workplace surveillance acted as a flashpoint around which feminist and legal allies could mobilize in support of exploited immigrant women in the textile industry during the 1970s. By the strike’s end, the Puretex women had not only gained invaluable and transformative strike experience but engaged with industrial legality and the state in a way that brought about meaningful change in their workplace. The Puretex strike is therefore a significant case of immigrant women’s militant organizing in the labour and feminist movements during the 1970s and an important reminder that engagement with industrial law and the state, in certain historical contexts, can provide avenues for successful worker resistances.